Native Forest Replacement by Exotic Plantations Triggers Changes in Prey Selection of Mesocarnivores - Vergara-Egert, P; Moreira-Arce, D (Elsevier Ltd, 2015)
Replacement of native forests by forest plantations may change the composition and abundance of small mammals, thus influencing the foraging behavior of mesocarnivores in these human-created habitats. We assessed how differences in prey abundance between native forests and exotic plantations in southern Chile may explain the prey selection of four mesocarnivores, as analyzed from their scats. Using a spatial zero-inflated Poisson model, we determined that the abundance of most small mammals was lower in plantations than native forests, except for three common species, which had similar or larger abundances in exotic plantations. We assessed mesocarnivores prey selection by assessing the coefficients and log-ratios of use and availability of a Bayesian Resource Selection Function. We determined that in native forest, the preferences of kodkod (Leopardus guigna) for arboreal prey was stronger, whereas chilla fox (Pseudalopex griseus) and Darwin s fox (Pseudalopex fulvipes) exhibited a selective preference for ground prey. Darwin s fox also exhibited a habitat-dependent changes in their selection for Darwin s leaf-eared mouse (Phyllotis darwini), from a positive log ratio in native forest to a negative ratio in exotic plantations. Conversely, culpeo fox (Pseudalopex culpaeus) selected long-tailed colilargo (Oligoryzomys longicaudatus) and Chilean climbing mouse (Irenomys tarsalis) in plantations only, even though these prey were more abundant in native forests. Although mature commercial forest plantations may provide feeding grounds for mesocarnivores, depending on their species-specific ability to capture available prey, the decline of small mammal availability in plantations may modify the prey selection of mesocarnivores. © 2015 Elsevier B.V.